The Struggle over Migration Policy - Gil S. Epstein; Shmuel Nitzan (Institute for the Study of Labor (IZA), 2005)
In this paper we analyze the endogenous determination of migration quota viewing it as an outcome of a two-stage political struggle between two interest groups: those in favor and those against the proposed migration quota. We first compare the proposed policies of the two interest groups under random behavior of the government, with and without lobbying. The paper proceeds with the examination of the effect of government intervention in the proposal of the quota on its nature, assuming that, with and without government intervention, the uncertain approval of the proposal is the outcome of a lobbying contest between the two interest groups. Finally, we examine the effect that the status-quo policy has on the proposed government's policy.
Keywords: J81; J61; 330; migration quota; interest groups; government intervention